2020
DOI: 10.3171/2020.4.peds2098
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy surgery for Rasmussen encephalitis: the UCLA experience

Abstract: OBJECTIVERasmussen encephalitis (RE) is a rare inflammatory neurological disorder typically involving one hemisphere and resulting in drug-resistant epilepsy and progressive neurological decline. Here, the authors present seizure outcomes in children who underwent epilepsy surgery for RE at a single institution.METHODSThe records of consecutive patients who had undergone epilepsy surgery for RE at the UCLA Mattel Children’s Hospital between 1982 and 2018 were retrospectively reviewed. Basic demographic informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
3
8
0
Order By: Relevance
“…In the present series, females predominated (58.1%). Previous series reported an equal sex distribution: 114 of 228 pooled patients in eight nonoverlapping series with >15 patients were female (50.0%) 12,16,20–25 . This may be related to their younger age at onset; in the present series, too, the younger patients had an equal sex distribution.…”
Section: Discussionsupporting
confidence: 46%
See 3 more Smart Citations
“…In the present series, females predominated (58.1%). Previous series reported an equal sex distribution: 114 of 228 pooled patients in eight nonoverlapping series with >15 patients were female (50.0%) 12,16,20–25 . This may be related to their younger age at onset; in the present series, too, the younger patients had an equal sex distribution.…”
Section: Discussionsupporting
confidence: 46%
“…Previous series reported an equal sex distribution: 114 of 228 pooled patients in eight nonoverlapping series with >15 patients were female (50.0%). 12,16,[20][21][22][23][24][25] This may be related to their younger age at onset; in the present series, too, the younger patients had an equal sex distribution. A review of late onset RE, by contrast, showed a 4:1 female preponderance.…”
Section: Demographic Datasupporting
confidence: 42%
See 2 more Smart Citations
“…The existing literature primarily consists of retrospective studies with small sample sizes. [6][7][8][10][11][12][13] Patients commonly have limited clinical data, become lost to follow-up, or studies feature multiple surgery types (hemispherectomy, hemispherotomy, or single lobar resection). Except for a single study examining 5 total patients who all underwent functional hemispherectomy between 1978 and 1981, no existing literature assesses outcomes of patients with RE who all received hemispherectomy.…”
Section: Discussionmentioning
confidence: 99%